Cultural image of the city of Lodz as depicted in “Wymiary” (1938–1939), social and literary monthly magazine - Bańkowska, Małgorzata (Interdyscyplinarium nauk o mediach i kulturze, 2020)
In the late 1930’s the flourishing city of the so-called Polish Manchester witnessed the birth of The Society for Arts and Literature with its hallmark monthly of “Wymiary” (“Dimensions”), published from April 1938 till June 1939. Bringing together left-wing authors and those openly advocating Jozef Pilsudski’s political doctrine, the magazine called for a universal access to cultural goods and promoted the ideology of regionalism. Acting in the capacity of The Society’s press organ, the periodical also supported the officially proposed concepts of cultural development of the “evil city” while setting guidelines on how to clean up the city’s somewhat tarnished image. The journalistic analysis of press releases from 12 issues offered an opportunity for recreating the cultural life of Lodz in the 1930s and dropped numerous hints about procultural activity embarked on by both – the local government and the literary community. In keeping with the objectives of the research, this article outlines the undertakings pursued by the key cultural and media institutions, as well as by scientific associations and educational organizations. Apart from that, projects of urban development of the city of Lodz have been presented.